(untitled) (Theatrum historiae, 2016)
The article presents the output of Polish historiography concerning the research on Cracow horoscopes created before the year 1550, that is, in the period of the most active development of astrology as an academic science at the University of Krakow. At that time, astrology was a subject of enormous interest, which was reflected by the fact that horoscopes were ordered from professional astrologers (because of the price of the service, this was done mostly by wealthy people). These horoscopes were supposed to, according to popular views at that time, show the future. This, particularly with regard to the royal family, affected the policies of the ruler, and often the fate of the whole country.